FIRST-ORDER LINEAR DIFFERENTIAL EQUATIONS. BERNOULLI'S DIFFERENTIAL EQUATION - Memonova Gulnoza Nazrikulovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The first-order linear differential equation is an important topic in the field of differential equations. This scientific paper provides an introduction to these equations, explaining what they are and how to solve them. Additionally, we delve into the Bernoulli differential equation and its transformations, which are a specific type of first-order nonlinear differential equation that can be transformed into a linear equation.